2023
DOI: 10.29026/oes.2023.220022
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal isolator in lithium niobate on insulator

Abstract: In this contribution, we simulate, design, and experimentally demonstrate an integrated optical isolator based on spatiotemporal modulation in the thin-film lithium niobate on an insulator waveguide platform. We used two cascaded travelling wave phase modulators for spatiotemporal modulation and a racetrack resonator as a wavelength filter to suppress the sidebands of the reverse propagating light. This enabled us to achieve an isolation of 27 dB. The demonstrated suppression of the reverse propagating light m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This integrated realization represents a three order of magnitude decrease in optical path length compared to typical 13.5 m optical ber loop setups [14], albeit at the cost of a corresponding increase in the relevant process rates from megahertz to gigahertz scale. Sub-1 dBcm − 1 propagation loss waveguides are fabricated by using a strip-loading approach, in which mode con nement is established by a 1 µm wide ridge patterned in a 300 nm thick silicon nitride lm covering the likewise 300 nm thickness LiNbO 3 layer [24,25], resulting in a stack sketched in Fig. 1b.…”
Section: Resultsmentioning
confidence: 99%
“…This integrated realization represents a three order of magnitude decrease in optical path length compared to typical 13.5 m optical ber loop setups [14], albeit at the cost of a corresponding increase in the relevant process rates from megahertz to gigahertz scale. Sub-1 dBcm − 1 propagation loss waveguides are fabricated by using a strip-loading approach, in which mode con nement is established by a 1 µm wide ridge patterned in a 300 nm thick silicon nitride lm covering the likewise 300 nm thickness LiNbO 3 layer [24,25], resulting in a stack sketched in Fig. 1b.…”
Section: Resultsmentioning
confidence: 99%
“…In non-Majorana devices, it has been experimentally demonstrated that Cooper pairs can be split into spin-entangled electrons flowing in two spatially separated normal metals, resulting in a positive current-current correlation. [26][27][28][29][30][31] Although there are many theoretical studies devoted to investigate the property of noise CC induced by MBSs, [32][33][34][35][36][37][38][39] the Majoranamodulated nonlocal transport has not been reported up to date. One of the possible reasons is that the Majorana energy splitting, which is essential to induce the noise CC, is generally weak and approaches to zero in some cases.…”
Section: Introductionmentioning
confidence: 99%